Digital Breast Tomosynthesis: Potential Benefits in Routine Clinical Practice. Issue 1 (February 2022) - Kulkarni, Supriya; Freitas, Vivianne; Muradali, Derek
Digital breast tomosynthesis (DBT) is gradually being implemented in routine clinical breast imaging practice. The technique of image acquisition reduces the confounding effect of overlapping breast tissue, which substantially affects cancer detection, abnormal recall, and interval cancer rates in a screening/ surveillance setting. In a diagnostic setting, tomosynthesis also allows for improved lesion localization and characterization over conventional imaging, which potentially improves the accuracy and improved workflow efficiency. To optimize the utility of tomosynthesis, imagers should be aware of the pertinent aspects of image acquisition as it relates to interpretation, the appearance of benign and malignant pathologies, and sources of possible misinterpretation. This article aims to provide a practical knowledge base of DBT and demonstrate its potential benefits when incorporated into routine clinical practice.